Online engineering education - A new approach in using physical laboratories to enhance student learning - Eleftheriou, Polyvios; Michaelides, Ioannis (My University, 2008)
This paper presents the experience from the operation of the solar energy e-learning laboratory in Cyprus and demonstrates the benefits of online engineering education in the field of solar energy. The solar energy e-learning laboratory (Solar e-lab) provides online experimentation, thus allowing students from anywhere to operate remote instruments at any time. The Solar e-lab comprises a pilot solar energy conversion plant which is equipped with all necessary instrumentation, data acquisition, and communication devices needed for remote access, control, data collection and processing. The installed hardware and software include features for controlling external devices, responding to events, processing data, creating report files, and exchanging information with other applications. The Solar e-lab has so far been accessed by users from over 400 locations from 75 countries spread all over the world and continents [1]. Furthermore, a number of colleges and Universities use the solar e-lab as part of their training programmes, like for example the Royal Institute of Technology in Sweden, the Delmenhorst College in Germany, and the Higher Technical Institute in Cyprus. There is an interactive communication between the students of the above institutions and the solar e-lab helping them to accomplish the assigned work in due time.
Keywords: Remote engineering; E-learning; Solar energy